Urinary Biomarkers in Urological Oncology: From Biological Origin to Clinical Decision-Making—A Narrative Review - Aliya Nurmukhanbetova; Kassymkhan Sultanbekov; Khussan Umurzakov; Zie Gassanov; Altyn Duisenbayeva; Alimkhan Talas; Lazzat Shaikenova; Aidos Bolatov (Diagnostics, 2026)
Urinary biomarkers are promising tools in urological oncology because urine can be collected non-invasively and repeatedly during diagnosis, treatment, and surveillance. Despite extensive biomarker discovery, their adoption in routine practice remains limited. Biomarker performance depends not only on analytical accuracy but also on the clinical decision, anatomical route into urine, biological source of the signal, specimen fraction, and timing and conditions of sampling. This review evaluates urinary biomarkers across bladder cancer, upper-tract urothelial carcinoma, prostate cancer, and renal cell carcinoma using a biologically grounded, decision-oriented framework. It considers tumor-derived nucleic acids, epigenetic alterations, proteins, immune and inflammatory mediators, extracellular vesicles, metabolites, microbiome-associated signals, and multiparametric models. Bladder cancer represents the most anatomically direct and clinically mature setting, with potential applications in hematuria evaluation, cystoscopy triage, recurrence surveillance, molecular residual disease assessment, and monitoring of response to bacillus Calmette–Guérin therapy. In upper-tract urothelial carcinoma, distinguishing voided from selectively collected urine is essential because dilution, transit, obstruction, and limited localization affect interpretation. Prostate urine assays are best positioned for biopsy triage and refinement of active surveillance rather than general population screening. Renal cell carcinoma biomarkers remain exploratory because the sources and mechanisms of urinary signal release are insufficiently resolved. Clinical translation should be assessed using decision-specific outcomes, including incremental value, calibration, net clinical benefit, procedures avoided, significant cancers missed, reproducibility, and feasibility, rather than diagnostic accuracy or area under the receiver operating characteristic curve alone.